Dendrite-free and corrosion-resistant sodium metal anode for enhanced sodium batteries - Lu, Qiongqiong; Omar, Ahmad; Hantusch, Martin; Oswald, Steffen; Ding, Ling; Nielsch, Kornelius; Mikhailova, Daria (Applied Surface Science, 2022)
Because of the high theoretical special capacity, low cost, and low redox potential of sodium (Na) metal, it has been regarded as an ultimate anode for high-energy–density Na metal batteries. Nevertheless, Na metal suffers from dendrite formation due to a non-uniform Na deposition and unstable interface between Na and electrolyte, resulting in a short circuit and low Coulombic efficiency. Herein, a Zn coating on the Na metal surface as a nucleation and protective layer was fabricated through an in-situ chemical method involving a simple dripping ZnCl2-tetrahydrofuran solution. The Zn coating endows Na with corrosion-resistance in organic ether-based electrolytes and a polysulfide solution. More importantly, Zn coating on Na enables a low nucleation overpotential due to its sodiophilic property, giving rise to a uniform Na deposition. Consequently, Zn-coated Na showed a stable cycling over 1200 h at 1 mA cm−2 with a high capacity of 2 mA h cm−2 in symmetric cells. When combined with Na3V2(PO4)3 cathode, full cells with Zn-coated Na demonstrated a good cycling stability and rate capability. This work presents a simple, effective and promising approach of designing a dendrite-free and corrosion-resistant Na metal anode for enhanced Na metal batteries.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Nucleation layer; Sodium dendrite; Sodium metal anode; Sodium metal batteries; Zn coating